2016
DOI: 10.1093/humrep/dew072
|View full text |Cite
|
Sign up to set email alerts
|

The value of fine needle aspiration cytology diagnosis in ovarian masses in children and adolescents

Abstract: NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
1
4
1
Order By: Relevance
“…The results of the current study are comparable to those of most other studies (Table ) . The high sensitivity seen in the studies by Pal et al and Uguz et al most likely are due to the high prevalence of malignancy in their study populations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of the current study are comparable to those of most other studies (Table ) . The high sensitivity seen in the studies by Pal et al and Uguz et al most likely are due to the high prevalence of malignancy in their study populations.…”
Section: Discussionsupporting
confidence: 88%
“…The results of the current study are comparable to those of most other studies (Table 4). [3][4][5][7][8][9][10][11][12][13][14][15] The high . Follicular cysts, consistent with their identity as nonneoplastic functional cysts, typically contained rare granulosa cells within a background of granular material.…”
Section: Cancer Cytopathologymentioning
confidence: 99%
“…We also included future study questions indicated by authors and a summary of two systematic reviews that met our criteria concerning the topic. We considered them to be helpful as, to our knowledge, these are the only systematic reviews regarding all kinds of ovarian masses in the last 10 years, and this type of research has a higher level of evidence (Level V) than any separate retrospective study [2,4,6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Our charting exercise revealed 10 major branches of research within the topic of ovarian masses in pediatric population: epidemiology and presentation, tumor markers, choice of the imaging method, risk factors for malignancy, risk of torsion and its low malignancy risk, use of laparoscopy, surgeon's specialty and outcome, rate of oophorectomy, and need for prospective study.…”
Section: Results Of the Scoping Studymentioning
confidence: 99%
“…The overall sensitivity and specificity of FNA biopsy of ovarian lesions is controversial and varies depending on individual studies. [71][72][73] FNA cytology diagnostic accuracy of ovarian tumor histotype is 52%. 74 In general, FNA biopsy has a higher yield in solid or solidcystic lesions in comparison to purely cystic lesions, which are typically paucicellular.…”
Section: Ovarian Epithelial Neoplasmsmentioning
confidence: 99%